Maternity Health Workers’ Views on the Effect of Social Conditions on The Maternal Mortality Rate in Hyderabad District, Pakistan - Avais, Muhammad Abdullah; Narijo, Hamida; Parker, Mike; Bilal, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2023)
The objective of the study was to find out the leading social factors causing maternal mortality in Hyderabad district A total of 125 maternity health workers including qualified gynecologists /obstetricians and undergraduate trained obstetricians from Hyderabad district (Sindh, Pakistan) were interviewed on the effect of social conditions on the maternal mortality rate with a predesigned close ended questionnaire. The period of study was four months from November 2016 to February 2017. It has been found that majority of the respondents revealed that a good number of complicated maternity cases are refused for admission due to unavailability of required facilities to treat such patients. This is considered one of the major reasons for maternal mortality death. Unavailability of required transport on an urgent basis is considered yet another cause. Leading causes of maternal mortality were poverty 41.6%), negligence of family men (27.2%), illiteracy (12%), malnutrition (11.2%) and non-availability of medical facilities (8%) at the center of primary care. It is a fact that socio cultural factor does influence the maternal mortality. Our findings resonate with the findings elsewhere. This necessitates to take corrective measures to improve the healthcare conditions of pregnant mother.